This American moment : a feminist Christian realist intervention - Gentry, Caron E. (Oxford studies in gender and international relations., 2018)
This American Moment looks at the anxieties that plague American politics, including those that deny the importance of Black Lives Matter and support the subordination of women, particularly as they relate to the election and continued support of President Trump. The book proposes feminist Christian realism, an update on Reinhold Niebuhr's Christian realism, as a way to re-engage the importance of love and relationships in politics.